Organizational Commitment of University Staff and Lecturers: A Case Study of Mahamakut Buddhist University - Channuwong, Sukhumpong (Journal of Community Development Research (Humanities and Social Sciences); Vol 8 No 3 (2558): September - December 2015, 2015)
Organizational commitment is a positive feeling of employees towards their organization. Employees with high organizational commitment will contribute their effort and work to achieve the goals and objectives of organization; they are the most important part to the success of an organization. The purposes of this research were: (1) to study an organizational commitment of university staff and lecturers; (2) to find a difference in organizational commitment of university staff and lecturers classified by demographic profile; (3) to find a relationship between factors influencing organizational commitment and organizational commitment of university staff and lecturers; and (4) to find the most important factors influencing organizational commitment of university staff and lecturers. The population and samples in this study were 212 participants who were staff and lecturers of Mahamakut Buddhist University. The results of the study showed that, in total, an organizational commitment of university staff and lecturers can be interpreted as highly committed. In particular, university staff and lecturers are highly committed to maintaining organizational reputation, followed by job satisfaction, maintaining organizational citizenship, and accepting and following the rules and regulations of organization respectively. The results of hypothesis testing showed that university staff and lecturers differing in gender and educational level had no different organizational commitment. University staff and lecturers differing in age group, marital status, monthly income, and work experience had different organizational commitment. There was a positive relationship between factors influencing organizational commitment and organizational commitment of university staff and lecturers. Job security was the most important factor influencing organizational commitment, followed by happiness at workplace, co-worker relationship, and benefits and compensation respectively. Recommendations for this research are as follows: The university should encourage staff and lecturers to fully express their knowledge and potential beneficial to improve their work performance. The university should explain the reasons to staff and lecturers if rules and regulations have to be changed appropriately for the growth and development of the university; by this way, staff and lecturers will be satisfied with changes in rules and regulations of the university respectively. In addition, the university should consider benefits and compensations as the main factors for staff and lecturers to work in the university over the long run.   Keywords: Education, Organizational Commitment, University Staff and Lecturers
Keywords: Education, Organizational Commitment, University Staff and Lecturers